Useful kicking foot behaviour of soccer instep kicking to launch the ball in various dircetions - Koichiro, I.; Hiroyuki, N. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
The present study aims to illustrate the distinct characteristics of foot motion at ball impact, manipulating various ball launch directions. Seven experienced male university players conducted a total of 126 trials of soccer instep kicking, targeting three areas of the soccer goal. Three ultra-high-speed cameras recorded the ball impact aspect at 2000 Hz. We computed the foot contact point, the foot instep direction, and the foot swing direction. The multiple regression model demonstrated that the variance of ball launch directions was explained significantly by the foot contact point and the foot instep direction, while the foot swing direction was not. This result suggested that the foot contact point on the ball and the instep facing directions must be controlled appropriately to facilitate players to kick the ball in the desirable directions.